The Timing of Timezyme Diversification in Vertebrates - Cazaméa-Catalan, Damien (PLoS One, 2014)
All biological functions in vertebrates are synchronized with daily and seasonal changes in the environment by the time keeping hormone melatonin. Its nocturnal surge is primarily due to the rhythmic activity of the arylalkylamine N-acetyl transferase AANAT, which thus became the focus of many investigations regarding its evolution and function. Various vertebrate isoforms have been reported from cartilaginous fish to mammals but their origin has not been clearly established. Using phylogeny and synteny, we took advantage of the increasing number of available genomes in order to test whether the various rounds of vertebrate whole genome duplications were responsible for the diversification of AANAT. We highlight a gene secondary loss of the AANAT2 in the Sarcopterygii, revealing for the first time that the AAANAT1/2 duplication occurred before the divergence between Actinopterygii (bony fish) and Sarcopterygii (tetrapods, lobe-finned fish, and lungfish). We hypothesize the teleost-specific whole genome duplication (WDG) generated the appearance of the AANAT1a/1b and the AANAT2/2′paralogs, the 2′ isoform being rapidly lost in the teleost common ancestor (ray-finned fish). We also demonstrate the secondary loss of the AANAT1a in a Paracantopterygii (Atlantic cod) and of the 1b in some Ostariophysi (zebrafish and cave fish). Salmonids present an even more diverse set of AANATs that may be due to their specific WGD followed by secondary losses. We propose that vertebrate AANAT diversity resulted from 3 rounds of WGD followed by previously uncharacterized secondary losses. Extant isoforms show subfunctionalized localizations, enzyme activities and affinities that have increased with time since their emergence.